Penggunaan Media Kartu Dalam Meningkatkan Penguasaan Kosa Kata Bahasa Arab Di Kelas X IPA 1 MAN 2 Halut - Nuryati Beddu; Sumiati Taib (EDUKASI, 2023)
Learning media are teaching aids for generating interest, visual enjoyment, facilitating the attainment of learning objectives, facilitating, understanding and remembering the information contained and motivating learning. Media plays an important role in the learning process. The purpose of this study was to determine the use of card media in increasing vocabulary mastery in Arabic and maximizing students' memory, activeness and motivation in learning in class X IPA 1 Madrasah Aliyah Negeri 2 Halmahera Utara. The research method used was a qualitative descriptive method with research subjects being class X IPA 1 Madrasah Aliyah Negeri 2 Halmahera Utara, totaling 22 students. Data collection techniques consisted of observation, oral tests and interviews. This research was conducted in 2 meetings which began with learning without using card media and using card media. The results of the study show that the use of card media is very effective in learning Arabic, because it can increase students' vocabulary mastery (mufradat). And the use of card media in learning Arabic can train students to maximize student memory and can create activeness and motivate students in learning.